Molecular Modeling and Spectroscopic Studies on the Interaction of Transresveratrol with Bovine Serum Albumin - Xiaoli Liu; Yonghui Shang; Xudong Ren; Hua Li (Journal of Chemistry)
The interaction of transresveratrol (TRES) with bovine serum albumin (BSA) has been investigated by ultraviolet-visible, fluorescence, Fourier transform infrared spectroscopic methods and molecular modeling techniques. The fluorescence results show that the intrinsic fluorescence of BSA is quenched by TRES through a static quenching procedure. The binding constants of TRES with BSA at 292, 297 and 302 K are calculated as 10.22×104, 8.71×104, and 7.59×104 L mol−1, respectively, and corresponding numbers of binding sites are approximately equal to unity. The thermodynamic parameters ΔH and ΔS are estimated to be −21.82 kJ mol−1 and +21.15 J mol−1 K−1, which indicates that the interaction of TRES with BSA is driven mainly by hydrophobic forces and there are also hydrogen bonds and electrostatic interactions. The competitive experiments suggest that the binding site of TRES to BSA is probably located on site II. The results of infrared spectra show that the binding of TRES with BSA leads to conformational changes of BSA, and the binding stabilizes the α-helix and β-sheet at the cost of a corresponding loss in the β-turn structure of BSA. The results of molecular modeling calculation clarify the binding mode and the binding sites which are in good accordance with the experiment results.